(untitled) (Journal of the College of Languages (JCL), 2014)
The literature in general, such as the spanish literature as british literature presence lot of literary figures giant that managed its continuing work that leaves lasting impression and clear in all fields of literary world throughout history, among these writers giants can remind great writer spanish (Miguel de Cervantes) and the great british writer (William Shakespeare), this study is about them. We can say that there are a lot of studies , works and gossip , whether literary or non- literary show how the close relationship that bound both Cervantes and William Shakespeare, although they did not meet personally never, it was not able to critics that the sweep of the differences and similarities that was between the two, because of the intelligence and the genius in various forms of everyday life has made a great affinity between them in relation to a literary work accurately and innovation of its take it out of the public the best of its quality and impact those around him and the depth of its originality. It is a spiritual relationship rather than a relationship or mock formality inspired by their actions that they have a timeless writing over their lives , such as ( Don Quijote writer Cervantes ) and ( writer Shakespeare’s Hamlet ). However, it is a big mistake if we set this relationship literary or framed a certain framework, they are an eternal and great expression of a there idealism literary and interdependent and their relationship with all that is human.